Case report of iatrogenic cerebral amyloid angiopathy after exposure to Lyodura: an Australian perspective - Muller, Claire (Frontiers in Neuroscience, 2023)
Background Recently proposed diagnostic criteria for iatrogenic cerebral amyloid angiopathy (iCAA) have sparked increased recognition of cases across the globe. Whilst these patients tend to have a tumultuous course, much like sporadic CAA, there is a high degree of variability. What is unique in this case is the breadth of clinicoradiological data available, including handwritten surgical notes from 1985. In retrospect, early imaging changes of what would ultimately lead to profound morbidity, were apparent 30 years after inoculation with cadaveric dural tissue. Aim In this case study we examine the clinicoradiological features of a case of probable iCAA and draw awareness to the presence of this disease in Australia. Methods This case was admitted under the care of the author at the Royal Brisbane and Women's Hospital (RBWH). Clinical details and data were gathered during the patient's care and consent for publication provided by the enduring power of attorney. Results This 56-year-old female presented in 2018 with left hemiparesis, neglect, and dysarthria secondary to a large right frontal lobe intracerebral hemorrhage (ICH) without an underlying macrovascular cause. MRI brain demonstrated diffuse superficial siderosis assumed related to previous surgical interventions during the mid-1980s for a Chiari malformation and cervical syrinx. There was evidence of extensive white matter disease, discordant with her lack of cerebrovascular disease risk factors. Brain biopsy confirmed CAA. Archived surgical notes confirmed exposure to Lyodura in 1985 and 1986. Two decades of MRI data were available for review and illustrate the evolution of CAA, from normal post-operative findings to marked and unrecognized abnormalities 4 years prior to her first ICH. Discussion This is the first Australian case of probable iatrogenic CAA (iCAA) to have such extensive documentation of clinicoradiological evolution. It demonstrates the aggressive course iCAA can take and provides insights into early disease manifestations, relevant to the more common sporadic cases. A brief review of the history of commercial cadaveric tissue use in Australia highlights enormous changes in medical practice over the last 50 years. Awareness within Australia should be raised for this clinical phenomenon, and cases collated to contribute to the growing international pool of evidence.